Prevalence and associated factors of unilateral spatial neglect among patients with stroke at Mbarara Regional Referral Hospital, Uganda: a cross-sectional study - Asiimwe Derrick; Migisha Richard; Nuwahereza Amon; Nkoyooyo Dauglas; Lubwama Conrad; Namayanja Rosemary; Omolo Ouma Ronald; Martha Sajatovic; Josephine Nambi Najjuma; Mark Kaddumukasa; Elly Katabira; Kira Bullock; et al. (BMC Neurology, 2026)
Background Unilateral spatial neglect (USN) is a common neurocognitive deficit following stroke and is associated with impaired rehabilitation and functional outcomes. Evidence on its burden and associated factors in low- and middle-income countries remains limited. This study determined the prevalence of USN and its associated factors among patients with stroke at Mbarara Regional Referral Hospital (MRRH), southwestern Uganda. Methods We conducted a cross-sectional study from August 12 to December 15, 2024. Patients with a recent stroke event within the preceding 0–4 months receiving care at MRRH were enrolled using consecutive sampling. Patients who were unable to see, aged <18 years or had bilateral stroke were excluded. USN was assessed using the Sunnybrook Neglect Assessment Procedure (SNAP): scores >5 indicating USN. Sociodemographic, clinical, and lifestyle factors were collected via structured questionnaires. Multivariable modified Poisson regression was used to identify factors associated with USN, reporting adjusted prevalence ratios (aPR) with 95% confidence intervals (CI). Results We enrolled 116 participants with a median age of 68 years (inter-quartile range [IQR]: 56–78). Most were female (65.5%). The prevalence of USN was 54.3% (n=63; 95% CI: 44–63). Among participants with USN, 60.4% were in the acute phase and 39.6% were in the subacute phase. Factors independently associated with a higher prevalence of USN included severe stroke (aPR=1.47), right-hemisphere lesions (aPR=1.58), and age ≥60 years (aPR=1.66), while right-handedness was associated with a lower prevalence of USN (aPR=0.94). Conclusion This study revealed a high prevalence of USN among patients with stroke at a referral hospital in southwestern Uganda. Stroke severity, right-hemisphere lesions, advanced age, and right-handedness were associated with USN. Targeted rehabilitation and early screening for patients with stroke with risk factors, particularly those with severe strokes or advanced age, could optimize recovery and improve long-term outcomes.
Keywords: Unilateral spatial neglect; stroke; prevalence; cerebrovascular disorders; Stroke rehabilitation; Uganda